Interpretation and prediction of optical properties: novel fluorescent dyes as a test case - Li, Xinxing; Yin, Xiuping; Bai, Yue-Ling; Biczysko, Malgorzata (Frontiers in Physics, 2023)
The rapid development of modern quantum mechanical theories and computational resources facilitates extended characterization for molecular systems of increasing size and complexity, including chromophores relevant for biochemical or technological interest. Efficient and accurate computations of molecular structure and properties in the ground and excited electronic states are routinely performed employing Density functional theory (DFT) and its time-dependent (TD-DFT) counterpart. However, the direct comparison with experiment requires simulation of electronic absorption or emission spectra, for which inclusion of vibrational effects leads to more realistic line-shapes, at the same time allowing for more reliable interpretation and prediction of optical properties, providing additional information which is not available from experimental low resolution UV-vis spectra. Computational support can help identifying the most interesting chromophores among a large number of potential candidates for the design of new materials or sensors, as well as unraveling effects contributing to the overall spectroscopic phenomena. In this perspective recently developed viologen derivatives, are selected as test cases to illustrate advantages of spectroscopic theoretical methodologies, which are still not widely used in "chemical" interpretation. These molecules are characterized by improved stability as well as the dual function of chromism and luminescence, but their detailed spectroscopic characterization is hampered by the fact that only low resolution experimental spectra are available. DFT based absorption and emission spectra are exploited in the analysis of optical properties, allowing detailed analysis of vibrational effects and gaining more insights on the structure-spectra relationship which can be extended to develop further viologen dyes with improved optical properties.